Postures “antipornography” and “anticensorship” in feminism. A reflection on their differences and similarities - Alpízar Lobo, Natasha (2021)
Introduction This essay raises a discussion about the “anti-pornography” and “anti-censorship” feminism tendencies in the pornography. Some of the differences between both are pointed out, but the central contribution will be in the pointing of proximities as both lines conceive pornography as an image or object (finished), where there is no transcendence in the way of understanding. Objective The main objective is to compare and to describe two of the most important positions when trying to think and investigate pornography from feminism. Method A systematization of classic and contemporary references was carried out on the Mendeley reference manager and for its more in-depth categorization an Excel document was used. Results In general, the academic references consulted insist on the sociohistorical differences, on the notions about sexuality and the pornography that exist between the “anti-pornography” and “anti-censorship” positions. However, the similarities and continuities among themselves are rarely problematized, which are associated to the ubication of pornography as an imagen or object. Conclusion In the closing, the essay proposed that it is necessary to read pornography as a relational process in constant unfolding (unfinished), not simply as an image or object.